2023
DOI: 10.1039/d3nj00491k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced desalination performance in flow electrode capacitive deionization with nitrogen doped porous carbon

Abstract: As a promising continuous desalination technology, flow electrode capacitive deionization (FCDI) has received considerable attention. However, poor conductivity and dispersion of the traditional active carbon (AC) flow-electrode limit the properties...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The peaks of C 1s and O 1s were almost unchanged as seen in Figures S5c and S4d. The distributions of the peaks in Figure S5c correspond to C–C, C–O, CO, and O–CO with binding energies of 284.8 eV, 286.28 eV, 288.68, and 290.58 eV, respectively. , The distribution of the peaks in Figure S5d corresponds to C–OH and CO with binding energies of 532.48 and 536.28 eV, respectively. ,, The XPS results also demonstrated that AC was not oxidized. This stable operation of FCDI was attributed to the voltage drop across all components of the FCDI cell .…”
Section: Resultsmentioning
confidence: 93%
“…The peaks of C 1s and O 1s were almost unchanged as seen in Figures S5c and S4d. The distributions of the peaks in Figure S5c correspond to C–C, C–O, CO, and O–CO with binding energies of 284.8 eV, 286.28 eV, 288.68, and 290.58 eV, respectively. , The distribution of the peaks in Figure S5d corresponds to C–OH and CO with binding energies of 532.48 and 536.28 eV, respectively. ,, The XPS results also demonstrated that AC was not oxidized. This stable operation of FCDI was attributed to the voltage drop across all components of the FCDI cell .…”
Section: Resultsmentioning
confidence: 93%